Autism Diagnostic Assessments With Children, Adolescents, and Adults Prior to and During the COVID-19 Pandemic: A Cross-Sectional Survey of Professionals - Spain, Debbie; Stewart, Gavin R.; Mason, David; Robinson, Janine; Capp, Simone J.; Gillan, Nicola; Ensum, Ian; Happé, Francesca (Frontiers in Psychiatry, 2022)
Background: Access to timely high quality autism diagnostic assessments has traditionally been patchy; many individuals wait months, if not years, for an appointment. The onset of the COVID-19 pandemic has likely impacted autism diagnostic services. This study investigated professionals’ experiences of, and thoughts about: (1) how autism diagnostic assessments were conducted before the pandemic; (2) adaptations to service provision because of the pandemic; and (3) challenges, risks, advantages and opportunities associated with autism assessments conducted via online platforms (telehealth). Method: Fifty-two professionals, based in different autism diagnostic services and working with children, adolescents and/or adults, completed an online cross-sectional survey in August and September 2020. This comprised demographic questions (about professionals’ roles and experiences), and closed and open questions about service provision and telehealth autism assessments. Results: There was substantial variation in how autism assessments were conducted prior to and during the pandemic; for example, in relation to the number of professionals involved in the assessment and types of structured, semi-structured and unstructured measures used to conduct this. Fifty-two percent of participants (n=27) reported some service disruption (e.g., full closure, substantial reduction in provision, and/or pausing of in person appointments). Waiting times for assessment had become longer for 58% of services (n=30), due to pandemic-related disruption. Six themes emerged from thematic analysis of open responses: (1) the autism diagnostic pathway, pre-pandemic; (2) initial impact of the pandemic on service delivery; (3) conducting autism assessments during the pandemic; (4) working remotely; (5) improving service design and delivery; and (6) post-diagnostic support. Views about the accessibility, validity and reliability of conducting telehealth autism assessments were polarised. Some participants considered this efficient, flexible and adequate; others viewed this as unethical and inappropriate. What constitutes good practice in telehealth autism assessments remains unclear, but there is a general openness to using this method (potentially in a hybrid telehealth – in person model), provided rigour and standardisation are enhanced. Conclusions: The pandemic has potentially compounded existing bottlenecks to the autism diagnostic pathway. Future research should seek to improve timeliness, standardisation, accessibility and robustness of this pathway, and the validity and reliability of telehealth autism assessments.